Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.

Role of dietary fatty acids in microglial polarization in Alzheimer's disease - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (2020)
Microglial polarization is an utmost important phenomenon in Alzheimer's disease that influences the brain environment. Polarization depends upon the types of responses that cells undergo, and it is characterized by receptors present on the cell surface and the secreted cytokines to the most. The expression of receptors on the surface is majorly influenced by internal and external factors such as dietary lipids. Types of fatty acids consumed through diet influence the brain environment and glial cell phenotype and types of receptors on microglia. Reports suggest that dietary habits influence microglial polarization and the switching of microglial phenotype is very important in neurodegenerative diseases. Omega-3 fatty acids have more influence on the brain, and they are found to regulate the inflammatory stage of microglia by fine-tuning the number of receptors expressed on microglia cells. In Alzheimer's disease, one of the pathological proteins involved is Tau protein, and microtubule-associated protein upon abnormal phosphorylation detaches from the microtubule and forms insoluble aggregates. Aggregated proteins have a tendency to propagate within the neurons and also become one of the causes of neuroinflammation. We hypothesize that tuning microglia towards anti-inflammatory phenotype would reduce the propagation of Tau in Alzheimer's disease.
Keywords: Fatty acids; Microglial polarization; Omega-3 fatty acids; Tau inflammation; Tau phagocytosis; Tau spreading; Tauopathy

Role of microglia in regulating cholesterol and tau pathology in alzheimer's disease - Nanjundaiah, Shwetha; Chidambaram, Hariharakrishnan; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Cholesterol, a principal constituent of the cell membrane, plays a crucial role in the brain by regulating the synaptic transmission, neuronal signaling, as well as neurodegenerative diseases. Defects in the cholesterol trafficking are associated with enhanced generation of hyperphosphorylated Tau and Amyloid-beta protein. Tau, a major microtubule-associated protein in the brain, is the key regulator of the mature neuron. Abnormally hyperphosphorylated Tau hampers the major functions related to microtubule assembly by promoting neurofibrillary tangles of paired helical filaments, twisted ribbons, and straight filaments. The observed pathological changes due to impaired cholesterol and Tau protein accumulation cause Alzheimer's disease. Thus, in order to regulate the pathogenesis of Alzheimer's disease, regulation of cholesterol metabolism, as well as Tau phosphorylation, is essential. The current review provides an overview of (1) cholesterol synthesis in the brain, neurons, astrocytes, and microglia; (2) the mechanism involved in modulating cholesterol concentration between the astrocytes and brain; (3) major mechanisms involved in the hyperphosphorylation of Tau and amyloid-beta protein; and (4) microglial involvement in its regulation. Thus, the answering key questions will provide an in-depth information on microglia involvement in managing the pathogenesis of cholesterol-modulated hyperphosphorylated Tau protein.
Keywords: Alzheimer's disease; Amyloid-beta protein; Cholesterol; microglia; Tau hyperphosphorylation

Role of cysteines in accelerating Tau filament formation - Chidambaram, Hariharakrishnan; Chinnathambi, Subashchandrabose (Journal of Biomolecular Structure & Dynamics, 2022)
Alzheimer's disease is majorly associated with intracellular accumulation of Tau into paired helical filaments and tangles. The self-aggregated dimeric and oligomeric species of Tau formed are more toxic to neuronal cells and acts as seeds for filament formation. The two cysteine residues and the two hexapeptide regions of full-length Tau play a key role in initialization and filament formation during Tau aggregation. The role of cysteine residues in Tau aggregation has been studied by in-vitro aggregation assay that was measured by Thioflavin S fluorescence to observe the kinetics of aggregation. In this study, we have performed in-vitro aggregation assay with recombinant full-length Tau and the cysteine mutants to understand the mechanism of cysteine independent Tau aggregation. Here, we report that cysteine mutant full-length Tau can aggregate to form filaments under in-vitro conditions. To visualize the polymorphisms of Tau and cysteine mutants under different aggregation conditions anionic cofactor, heparin was employed. Wild-type Tau showed rapid aggregation to form oligomers and filaments. On the other hand, the cysteine mutant delayed the initial Tau aggregation. This indicates the importance of cysteine residues in accelerating initial Tau nucleation for its aggregation. The filament morphology of wild-type and cysteine mutant Tau has been characterized using transmission electron microscopy and high-resolution transmission electron microscopy. Communicated by Ramaswamy H. Sarma
Keywords: Heparin-induced aggregation; Paired helical filaments; Tau Aggregation; Tau Oligomers; tau protein